Cervical cancer and precursors clinical and pathological correlations in a Lima’s periphery population - Valer, Victoria (2005)
Objective: To determine both the prevalence and risk factors of cervical cancer and squamous intraepithelial lesions, with special attention on the preinvasive cervical disease treatment. Design: Prospective, descriptive, non randomized study. Materials and Methods: Study of 120 non randomly selected cases of cervical cytology during 2003, in women attended at Piedra Liza Health Center (San Juan de Lurigancho). In 49 cases, biopsy was performed to confirm both clinical and colposcopic findings. Results: From the 120 cytology cases, 14 (11,5%) were ASC, 67 (56%) L-SIL, 34 (29%) H-SIL, 3 (2,5%) squamous carcinoma, 2 (2%) adenocarcinoma. In the 49 biopsies, 12 cases were L-SIL, 32 H-SIL, 3 invasive squamous carcinoma, and 2 cervical adenocarcinoma, one in situ. Conclusions: Cytology results suggest that squamous intraepithelial lesions and cervical carcinoma have higher prevalence in this study group.